Gypenosides, a promising phytochemical triterpenoid: research progress on its pharmacological activity and mechanism - Li, Xue; Chen, Yiwei; Wang, Ruyu; Cao, Baorui; Deng, Tingting; Han, Jinxiang; Yang, Meina (Frontiers in Pharmacology, 2025)
Gypenosides (Gyps), a group of dammarane triterpene saponins that are primarily from Gynostemma pentaphyllum, have been identified as promising natural compounds with a diverse array of potent pharmacological activities. In the past 2 decades, a growing body of evidence has demonstrated that Gyps are crucial for the regulation of metabolic homeostasis, the reduction of oxidative stress and inflammation, the protection of the cardiovascular and hepatic systems, and the exhibition of anti-cancer potential. However, obstacles such as limited oral bioavailability, a lack of standardized extracts, and insufficient clinical data restrict the translational potential of Gyps. Recent developments in the pharmacological effects of Gyps, such as the biological characteristics of Gynostemma pentaphyllum and the pharmacokinetic and toxicological properties of Gyps, are summarized in this review. We examine the current research limitations and prospective directions for Gyps as potential therapeutic drugs or functional supplements.